2022
DOI: 10.1002/cbic.202200443
|View full text |Cite
|
Sign up to set email alerts
|

Pi‐Class Glutathione S‐transferase (GSTP1)‐Selective Fluorescent Probes for Multicolour Imaging with Various Cancer‐Associated Enzymes

Abstract: Pi-class glutathione S-transferase (GSTP1) is highly expressed in a wide variety of human cancer tissues compared to the corresponding normal counterpart. Therefore, GSTP1 is a potential target enzyme for overcoming resistance to chemotherapeutic agents or visualizing specific lesions such as cancer.Here, we present orange and red fluorescence-emitting probes selective for GSTP1. Carbofluorescein and TokyoMagenta fluorophores were modified with a previously described GSTP1selective chromogenic compound to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Previous studies have clearly identified the elevated GGT levels in cancer, e.g., 494.5765 U/L of GGT in HeLa cells, while 5–85 U/L in blood of normal adult . Taking this fact into consideration, GGT has been explored as a potential diagnostic and prognostic biomarker for various cancers …”
Section: Applications Of Ggt-activatable Fluorescence Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have clearly identified the elevated GGT levels in cancer, e.g., 494.5765 U/L of GGT in HeLa cells, while 5–85 U/L in blood of normal adult . Taking this fact into consideration, GGT has been explored as a potential diagnostic and prognostic biomarker for various cancers …”
Section: Applications Of Ggt-activatable Fluorescence Materialsmentioning
confidence: 99%
“…39 Taking this fact into consideration, GGT has been explored as a potential diagnostic and prognostic biomarker for various cancers. 108 As introduced above, Urano and co-workers developed an "off−on" response fluorescence probe (γGlu-HMRG, Probe #1) for GGT measurement. The GGT could cleave the γglutamyl from γGlu-HMRG to release the fluorescent HMRG that was then rapidly internalized into cells and accumulated primarily in lysosomes to promote the fluorescence specifically in enzyme-expressing cells (Figure 2).…”
Section: Ggt-activatable Materials For Cancer Diagnosismentioning
confidence: 99%